Preterm Delivery Phenotypes in Systemic Lupus Erythematosus Pregnancies - Simard, Julia F.; Chaichian, Yashaar; Rossides, Marios; Wikstrom, Anna-Karin; Shaw, Gary M.; Druzin, Maurice L. (American Journal of Perinatology, 2019)
Objective Women with systemic lupus erythematosus (SLE) are at a greater risk of preterm delivery, many of which may be medically indicated (iatrogenic). We investigated preterm delivery phenotypes in SLE and general population comparators and assessed the role of preeclampsia.Study Design We used population-based Swedish Register data (2001–2013) and defined maternal SLE as ≥2 SLE-coded discharge diagnoses from the Patient Register with ≥1 coded by an appropriate specialist. Women from the general population were identified using the Total Population Register. Preterm delivery was defined as <37 weeks and separated into spontaneous and iatrogenic, as well as later versus extremely preterm (32 to <37 weeks vs. <32 weeks). Maternal comorbidity was assessed, and the proportion mediated by preeclampsia was calculated examining first, subsequent, and all pregnancies.Results Preterm delivery was more common in SLE for the first (22 vs. 6%) and subsequent (15 vs. 4%) pregnancies among 781 SLE-exposed pregnancies and 11,271 non-SLE pregnancies. Of SLE-exposed first births, 27% delivered before 32 weeks, and 90% were iatrogenic (compared with 47% of non-SLE first births).Conclusion Preterm delivery complicates a greater proportion of SLE pregnancies than general population pregnancies, and a considerable proportion of risk is mediated through preeclampsia.
Keywords: lupus; preterm birth; registers; preeclampsia